The Effect of Balance and Concentration Exercises on the Shooting Results of Petanque Riau Athletes - Solihin Solihin; Heny Setyawati; Taufiq Hidayah (JUARA : Jurnal Olahraga, 2022)
This study aimed to determine and analyze the effect of balance training on shooting results in Riau petanque athletes and the effect of concentration training on shooting results in Riau petanque athletes and investigating the effect of balance training and concentration training on shooting results in Riau petanque athletes. This study uses a quasi-experimental method with the research design "Two Group Pretest Posttest Design". The instrument used to test the shooting ability is the number game shooting station 1, 2, 3, 4, and 5 with a distance of 6 meters, 7 meters, and 8 meters. , and 9 meters. The subjects in this study were Riau Petanque athletes, totalling 32 sons, which were taken from the total sampling results. The results of this study: 1) There is an effect of balance training exercises on the shooting results of the Riau Petanque athletes. 2) there is an effect of concentration training on the shooting results of the Riau Petanque athletes. 3) there is an influence between balance training and concentration training on the shooting results of Riau petanque athletes. Based on the results of this study, it can be concluded that balance and concentration training significantly affect the shooting results of the Riau Petanque athletes based on the paired samples test. Then from the two exercises, the concentration exercise is better than the balancing exercise, based on the independent samples test. It can be interpreted that balance and concentration training influence the shooting results of the Riau Petanque athletes. Still, concentration exercises have.